Agrotechnical Requirements and Benefits of Fertilizing the Vine's Root System (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Timing of fertilizer application. Organic fertilizers should be applied in the fall at the same time as fall plowing so that over the winter they transform into a form easily absorbed by plants. Organic fertilizers applied in the spring have very little effect on the development of the grape plant, especially in dry weather, since they do not have time to completely decompose. If they still manage to completely decompose, the ammonia released can have a harmful effect on the development of grapes. Organic fertilizers are applied to sandy soil in early spring.In early spring, only well-rotted manure is applied to light sandy and sandy loam soils. During the first spring plowing, even before the grape bushes open, it is deeply plowed. Slow-acting mineral fertilizers are applied to the soil of vineyards at the end of winter, and fast-acting ones in the spring. For example, ammonium nitrate is applied in the spring, when the grape growing season begins.